Mycoplasma hominis and Ureaplasma urealyticum infections after knee arthroplasty: A case report. Issue 45 (11th November 2022) - Luo, Jingjing; Wu, Xinan; Gang, Xue; Zhang, Nana; Wang, Feifei; Rong, Chengting
Abstract : Rationale: Artificial joint infection caused by Mycoplasma hominis and Ureaplasma urealyticum is rare and has not been reported. Patients concerns: A 59-year-old man underwent left total knee arthroplasty for 1 year of pain in the left knee joint. The indwelling urinary catheter was removed after 48 hour of the surgery. On day 8 after the surgery, the patient had fever, increased skin temperature, swelling and redness around the surgical site, and floating patella test (+). According to experience, Vancomycin, Ciprofloxacin and Linezolid were administrated. Evident decrease in C-reactive protein was observed after Linezolid administration, while there was no significant improvement in clinical symptoms. Microbiome sequencing was performed, resulting in diagnosis of positive M hominis and U urealyticum . The patient was then treated with Doxycycline in the following 3 months. During the 11-month outpatient follow-up, there was no evidence of recurrence of infection. Diagnosis: Microbiome sequencing was performed, resulting in diagnosis of positive M hominis and Ureaplasma urealyticum. Interventions: The patient recovered following with Doxycycline in the following 3 months. Outcomes: During the 11-month outpatient follow-up, there was no evidence of recurrence of infection. Lessons: M hominis and U urealyticum are common pathogens of the urinary system infections but they are rare in osteoarticular infections. In cases of fever, swelling and heat pain around the surgical site, joint fluid, negative blood culture and being irresponsive to anti-bacterial agents against the cell wall, special bacteria-related infection should be highly suspected.